A Mathematical Model of Multipath QoS-based Routing in Multiservice Networks - Лемешко, О. В.; Drobot, O. (International conference TCSET’2006, 2006)
In this paper, an approach to the mathematical modeling of multipath QoS-based routing in multiservice networks is considered. The Gallager’s model was assumed as a basis of offered model with introduction of additional restrictions on quality of service. Tensor interpretation of model has allowed to receive in an analytical kind of a condition of maintenance of quality of service simultaneously on high-speed and time parameters QoS.
Keywords: Multiservice Network; Quality of Service; QoSbased Routing; Mathematical Model; Delay; Jitter